An Overview of the Issues for Recreational and Competitive Surf Lifesaving Injuries Associated With Inflatable Rescue Boats: Technical Report #6 to Surf Life Saving New Zealand (SLSNZ) - Diewald, SN; Hume, P; Wilson, BD; Wooler, A; Merrett, R; Fong, DTP; Reay, S; Smith, V; Keeley, L; Malpas, K (SPRINZ, Auckland University of Technology, 2019)
Background: Injuries to surf lifesavers operating inflatable rescue boats was identified as a problem by Surf Life Saving New Zealand (SLSNZ). However, the extent and nature of the injuries was not clear from internal SLSNZ reports. Purpose: To examine effects of factors influencing injury related to surf lifesavers operating inflatable rescue boats and to determine priorities for countermeasure interventions. It was hypothesised that susceptibility and risk of different injuries may vary between patrol duties and competition use of IRB, and between crew and driver. Methods: The systematic review of international published literature and screening process resulted in 26 articles published from 1971 to 2018 that met the inclusion and exclusion criteria. Epidemiological studies that examined surf lifesaving or water board‐sport related injuries were included. SLSNZ provided internal injury reports from 2013‐2017, along with the SLSNZ Inflatable Rescue Boat Manual and SLSNZ board meeting minutes. Results: There was a high incidence of lower limb injuries resulting from inflatable rescue boat operation according to the limited research. Navigating the surf and landing after aerial movements were frequent causes of injury. Susceptibility and risk to different injuries varied between patrol and competition forms of IRB use and between crew members and drivers. Discussion: Variation in methodological design made it difficult to compare international results. Potential injury risk factors include equipment design, driver experience, and crew technique, strength and experience, maturity and attitude of drivers. Conclusions: Susceptibility and risk to injuries varied between patrol and competition forms of IRB use and between crew members and drivers. Key risk factors identified from the studies included position in the IRB (crew or driver), lower body strength, and IRB equipment design.